Metode AHP-Fuzzy untuk Menentukan Tingkat Prioritas Tindak Pidana Penyalahgunaan Narkotika dan Psikotropika - Muzafanti, Rahmah Navi'ah; Alisah, Evawati; Rozi, Fachrur (Jurnal Riset Mahasiswa Matematika, 2024)
Analytical Hierarchy Process (AHP) is a method in decision making by analyzing multi-attribute decisions with many criteria and alternatives. these weaknesses, then the incorporation of fuzzy concepts is carried out, because there is a range of values that can cover the uncertainty of decision making in AHP. The merger of the two concepts is known as Analytical Hierarchy Process-Fuzzy or AHP-Fuzzy. The AHP-Fuzzy method uses an extended analysis with a triangular fuzzy membership function or TFN. Meanwhile, there is data on narcotics and psychotropic crimes. The data contains the indictment of each defendant containing the articles violated, prison sentences, and fines. Because it fulfills the AHP-Fuzzy method by having the main criteria. The author takes the formulation of the problem, namely the AHP-Fuzzy method to determine the priority level of criminal acts of narcotics and psychotropic abuse. This research aims to find out how the role of the AHP-Fuzzy method in criminal case data. The adjustment of the method when processing criminal offense data, producing the final result is at the stage of determining the crisp value and weighting. Before entering the crisp value determination stage, first determine the variables and the range of values that adjust the data conditions. Then, the weighting stage contains the results of the multiplication between AHP priority weights and weight vectors in fuzzy concepts. Thus, each of the main criteria has a different percentage priority level. The highest priority level is article 114, followed by article 112, article 111, and article 127. This priority level information can be used as a reference in preventing the spread of narcotics and psychotropic drugs, especially in Malang City.